A comparative study to evaluate the outcome between open posterior preperitoneal versus open anterior tension free hernioplasty in cases of recurrent inguinal hernia - Charpot, Rahul V.; Chauhan, Himesh R. (International Surgery Journal, 2016)
Background: The ideal method for repair of inguinal hernia would cause minimal discomfort to the patient, both during the surgical procedure and in the postoperative course. It would be technically simple to perform and easy to learn, would have a low rate of complications and recurrence, and would require only a short period of convalescence. However, the most effective method in any given patient is not clearly defined and consequently surgery for recurrent inguinal hernia after mesh repair is usually a difficult operation due to the disadvantage of re-operating through dense fibrotic scar tissue around the mesh with the risk of testicular damage and a large number of local hematoma. To avoid the disadvantage of re-operating through scar tissue and dense fibrotic scar tissue around the mesh, the open posterior pre peritoneal mesh repair was popularized by Nyhus as a good alternative for recurrent inguinal hernias. In previous study, Saber and co-workers reported that open pre peritoneal hernia repair offers many advantages over the trans inguinal repair for recurrent hernia. This approach gives results far superior to those of the commonly used anterior approach. Methods: Patients in this study were divided consecutively in two main groups: A and B. Group A patients were subjected to open posterior preperitoneal approach, those of group B were subjected to transinguinal anterior tension-free repair. All of our patients were gentlemen with total number was 60 patients; 30 for each group, their ages ranged between 42 and 65 years. The study duration was from January 2009 to January 2011 in department of general surgery, B.J Medical college and civil hospital, Ahmedabad, India. Results: There was no statistical difference between the two groups regarding patients’ age and body mass index. Age ranged between 42 and 65 years with a mean age as 53.5 years. The mean operative time in group A was 71.3 min±25.2 (40-120). In group B, the mean value was 94.5 min±28.5 (60-150). The mean hospital stay was 1- 3 days (2.1 ± 0.8) in group A and 2-6 days (3.7 ± 1.5) in group B. In the other hand, the mean time to return work was 8.2±1.15 (7-10) days in group A while in group B was 11.2 ± 2.3 (7-15) . Therefore, the mean time off from work in group A was 10.3 ± 1.95 days and in group B was 14.9±3.8 (P < 0.05).Chronic postoperative pain was observed in 4 patients in group A (13.33%) , in 9 patients in group B (30%). Conclusions: In recurrent inguinal hernia, the open posterior approaches are more effective in term of operative outcome. The open pre peritoneal hernia repair offers many advantages. It is inexpensive, has a low recurrence rate, and allows the surgeon to cover all potential defects with one piece of mesh. Postoperative recovery is short and postoperative pain is minimal. This approach gives results far superior to those of the commonly used anterior approach.